The mechano-ubiquitinome of articular cartilage: differential ubiquitination and activation of a group of ER-associated DUBs and ER stress regulators - Kaokhum, N; Pinto-Fernandez, A; Wilkinson, M; Kessler, BM; Ismail, H (Elsevier, 2022)
Understanding how connective tissue cells respond to mechanical stimulation is important to human health and disease processes in musculoskeletal diseases. Injury to articular cartilage is a key risk factor in predisposition to tissue damage and degenerative osteoarthritis. Recently, we have discovered that mechanical injury to connective tissues including murine and porcine articular cartilage causes a significant increase in lysine-63 polyubiquitination. Here, we identified the ubiquitin signature that is unique to injured articular cartilage tissue upon mechanical injury (the “mechano-ubiquitinome”). A total of 463 ubiquitinated peptides were identified, with an enrichment of ubiquitinated peptides of proteins involved in protein processing in the endoplasmic reticulum (ER), also known as the ER-associated degradation response, including YOD1, BRCC3, ATXN3, and USP5 as well as the ER stress regulators, RAD23B, VCP/p97, and Ubiquilin 1. Enrichment of these proteins suggested an injury-induced ER stress response and, for instance, ER stress markers DDIT3/CHOP and BIP/GRP78 were upregulated following cartilage injury on the protein and gene expression levels. Similar ER stress induction was also observed in response to tail fin injury in zebrafish larvae, suggesting a generic response to tissue injury. Furthermore, a rapid increase in global DUB activity following injury and significant activity in human osteoarthritic cartilage was observed using DUB-specific activity probes. Combined, these results implicate the involvement of ubiquitination events and activation of a set of DUBs and ER stress regulators in cellular responses to cartilage tissue injury and in osteoarthritic cartilage tissues. This link through the ER-associated degradation pathway makes this protein set attractive for further investigation in in vivo models of tissue injury and for targeting in osteoarthritis and related musculoskeletal diseases.